Effect of the Ratio of Protein to Water on the Weak Gel Nonlinear Viscoelastic Behavior of Fish Myofibrillar Protein Paste from Alaska Pollock - Timilehin Martins Oyinloye; Won Byong Yoon (Gels, 2024)
The linear and nonlinear rheological behaviors of fish myofibrillar protein (FMP) paste with 75%, 82%, and 90% moisture content were evaluated using small-amplitude oscillatory shear (SAOS) and large-amplitude oscillatory shear (LAOS) tests. SAOS revealed pastes with 75% and 82% moisture exhibited solid-like behavior, characterized by higher storage modulus (G′) than loss modulus (G″), indicative of weak gel properties with a strong protein interaction. In contrast, the 90% moisture content showed more viscous behavior due to weakened protein–protein entanglements. The frequency exponent (n′ and n″) from the power law equation varied slightly (0.24 to 0.36), indicating limited sensitivity to changes in deformation rate during SAOS. LAOS tests revealed significant structural changes, with Lissajous–Bowditch curves revealing early nonlinearities at 10% strain for 90% moisture content. Decomposed Chebyshev coefficients (e3/e1,v3/v1,S,andT) indicated strain stiffening at lower strains for the 75% and 82% moisture pastes (i.e., < 50% strain for 75% and < 10% strain for 82%), transitioning to strain thinning at higher strains. Additionally, numerical model confirmed the predictability of the 3D printing process from the nonlinear rheological data, confirmed the suitability of the 75% and 82% moisture pastes for applications requiring structural integrity. These insights are essential for optimizing processing conditions in industrial applications. The findings suggest that the 75% and 82% moisture pastes are suitable for applications requiring structural integrity, while the 90% moisture paste is ideal for flow-based processes. These insights are essential for optimizing processing conditions in industrial applications.